Central figures and events of Ukrainian history in the light of content analysis of the Ukrainian historical YouTube channels from 2014 to 2022 - Werner, Wiktor; Vovchuk, Liudmyla (My University, 2023)
The purpose of the research is to identify historical heroes and events that are top among the Ukrainians from 2014 to 2022, based on the processing of historical videos posted on the leading Ukrainian historical YouTube channels. The methodology of the research is based on a complexapproach, which implies the use of special computer methods that have not been used in this way before. The methods related to complex network analysis (CNA) have been used, with the help of which a relational database containing information about the most popular characters, events and topics in the Ukrainian historical YouTube videos was depicted in the form of a graph, and the most significant characters and motifs were found out by measuring centrality (as graph vertices). The Louvain Community Detection and Clauset_Newman_Moore algorithms have been used to extract links between topics and the context of their creation (date). The scientific novelty consists in the fact of finding out the renowned historical heroes among the users of Ukrainian historical YouTube channels owing to the use of innovative computer methods. The Conclusion. Nowadays, YouTube, it is not just a platform for posting relevant video content. It is a social network that serves as a platform for learning, communication, exchange of ideas, and distribution of important information. Diverse interesting and important films and videos appeared on the Ukrainian YouTube channels with historical themes in 2014 – 2022, regarding the coverage of the Ukrainian view of its own history, which was carefully hidden or rewritten by colonial regimes for decades. As a result of the research, owing to the cutting-edge computer methods application, the authors found out that the top period of Ukrainian history for domestic producers of video products posted on the Ukrainian segment of YouTube is the period of the 17th century. Accordingly, the top historical hero is Bohdan Khmelnytskyi. However, for the Ukrainian users of these YouTube channels, the top historical hero is Ivan Mazepa, a symbol of the struggle for the Ukrainian and European statehood. The conducted research showed that the interest of the Ukrainians in the history of their own country has increased recently. This tendency is could be observed with the outbreak of the full-scale Russian-Ukrainian War, which affected people’s reception of their own past significantly. And this is, in fact, the beginning of the conscious nation formation, who seeks to get rid of its “backwardness” and the imperial past, and aims at gaining self-respect and respect of the European community of peoples. It is the foundation for getting rid of the Ukrainians’ reception of themselves as the inferior. It is one of the important steps towards building a truly independent state, an equal partner in the international arena.
Analiza zawartości mediów cyfrowych z wykorzystaniem metody badania złożonych sieci (Complex Network Analysis). Przedmiotem badania jest reprezentacja postaci i wydarzeń z historii Ukrainy w mediach cyfrowych.
Keywords: Historical Ukrainian YouTube Channels; social media; digital media; historical consciousness; historical narrative; network analysis